A Microsized Cagelike Sulfur/Carbon Composite for a Lithium/Sulfur Battery with Excellent Performance. Issue 7 (14th May 2014) - Wang, Meiri; Zhang, Yining; Zhang, Hongzhang; Zhang, Huamin
Abstract A sulfur/carbon composite with a hollow cagelike configuration is synthesized and employed as a lithium/sulfur battery. The material provides a hierarchical porous structure with small pores in local regions and large pores connected to each other throughout the electrode. It exhibits a good polysulfide retention ability, promotes the efficient transfer of electrons and ions, and suppresses the redistribution of active material during cycles. Thus, the battery shows an improved rate performance, as well as a superior cycling stability of 94 % capacity retention, after 100 cycles at 0.5 C.